Lipoxin Receptors. (2007) - Romano, Mario; Recchia, Irene; Recchiuti, Antonio
Abstract : Lipoxins (LXs) represent a class of arachidonic acid (AA) metabolites that carry potent immunoregulatory and anti-inflammatory properties, LXA4 and LXB4 being the main components of this series. LXs are generated by cooperation between 5-lipoxygenase (LO) and 12- or 15-LO during cell-cell interactions or by single cell types. LX epimers at carbon 15, the 15-epi-LXs, are formed by aspirin-acetylated cyclooxygenase-2 (COX-2) in cooperation with 5-LO. 15-epi-LXA4 is also termed aspirin-triggered LX (ATL). In vivo studies with stable LX and ATL analogs have established that these eicosanoids possess potent anti-inflammatory activities. A LXA4 receptor has been cloned. It belongs to the family of chemotactic receptors and clusters with formyl peptide receptors on chromosome 19. Therefore, it was initially denominated formyl peptide receptor like 1 (FPRL1). This receptor binds with high affinity and stereoselectivity LXA4 and ATL. It also recognizes a variety of peptides, synthetic, endogenously generated, or disease associated, but with lower affinity compared to LXA4 . For this reason, this receptor has been renamed ALX. This review summarizes the current knowledge on ALX expression, signaling, and potential pathophysiological role. The involvement of additional recognition sites in LX bioactions is also discussed.